2009
DOI: 10.1038/leu.2008.352
|View full text |Cite
|
Sign up to set email alerts
|

Early related or unrelated haematopoietic cell transplantation results in higher overall survival and leukaemia-free survival compared with conventional chemotherapy in high-risk acute myeloid leukaemia patients in first complete remission

Abstract: Between 1996 and 2004, a total of 708 patients were enrolled in the acute myeloid leukaemia (AML) '96 and '02 studies of the East German Study Group (OSHO). Of these, 138 patients (19.5%) had unfavourable cytogenetics defined as complex karyotype, del (5q)/-5, del (7q)/-7, abn (3q26) and abn (11q23). In all, 77 (56%) achieved complete remission 1 (CR1) after induction chemotherapy and were eligible for haematopoietic cell transplantation (HCT). HCT was performed after a median of two cycles of consolidation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 23 publications
5
44
0
4
Order By: Relevance
“…Patients with good risk cytogenetics such as abn [16] or t(8; 21) can be spared from the toxicity of SCT, while patients with high risk cytogenetics appear to benefit from SCT, with an estimated 44% probability of surviving 5 years after CR1, compared with 15% or less after chemotherapy [2]. Several reports have confirmed this significant advantage of SCT in high risk AML, and it is currently highly recommended not to delay SCT in this population [3][4][5]. Among patients with high risk AML, the coexistence of multiple clonal cytogenetic abnormalities, referred to as complex karyotype (CK), has been associated with the worst outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with good risk cytogenetics such as abn [16] or t(8; 21) can be spared from the toxicity of SCT, while patients with high risk cytogenetics appear to benefit from SCT, with an estimated 44% probability of surviving 5 years after CR1, compared with 15% or less after chemotherapy [2]. Several reports have confirmed this significant advantage of SCT in high risk AML, and it is currently highly recommended not to delay SCT in this population [3][4][5]. Among patients with high risk AML, the coexistence of multiple clonal cytogenetic abnormalities, referred to as complex karyotype (CK), has been associated with the worst outcome [6].…”
Section: Introductionmentioning
confidence: 99%
“…56 Although a true comparison of matched sibling and matched unrelated donor HCT would require randomization of patients with sibling donors to receive transplant from the sibling or a matched unrelated donor such a trial is not feasible. With this constraint and bearing in mind, the increased difficulties with donor --no donor analyses in the unrelated setting, data suggest equivalent results with matched sibling and matched unrelated HCT 57,58 and that if HCT from a (living) matched unrelated donor is not feasible, double cord blood transplants are (at least) their equivalent. 59 The past 20 years have also seen the development of reduced intensity conditioning (RIC) regimens.…”
Section: Which Investigational Induction Therapy?mentioning
confidence: 81%
“…Recently, several groups have conducted prospective donor vs no-donor studies for AML patients with high-risk features by expanding the type of donor to include unrelated donors. [19][20][21] Notably, despite a limited number of patients in each study, they showed significantly superior OS in patients with a donor, as well as comparable OS in patients undergoing related and unrelated HCT. [19][20][21] These prospective studies also support the usefulness of unrelated HCT in younger AML patients with non-favorable cytogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Notably, despite a limited number of patients in each study, they showed significantly superior OS in patients with a donor, as well as comparable OS in patients undergoing related and unrelated HCT. [19][20][21] These prospective studies also support the usefulness of unrelated HCT in younger AML patients with non-favorable cytogenetics. Although our multivariate analysis showed that the degree to which allogeneic HCT had favorably affected outcome was less marked in patients without a related donor compared with those with a related donor, unrelated HCT could be considered a reasonable treatment option if a related donor is not available.…”
Section: Discussionmentioning
confidence: 99%